Halogenated thiophenes serve as solvent additives in mediating morphology and achieving efficient organic solar cells. Issue 12 (24th October 2022) - Guo, Lingzhi; Li, Qingduan; Ren, Jiaxuan; Xu, Yuanjie; Zhang, Jiabin; Zhang, Kai; Cai, Yuepeng; Liu, Shengjian; Huang, Fei
Abstract : Halogenated thiophene (FBrT) dissolves donor and acceptor readily, providing meaningful roles in mediating morphology. Thus, FBrT possesses general applicability in reaching efficient organic solar cells with improved fill factors and efficiencies. Abstract : Incorporating solvent additives in donor and acceptor solutions is an effective strategy for achieving efficient organic solar cells. As the state-of-the-art photovoltaic materials have thiophene sequences along their conjugated backbones, in this contribution, thiophene analogues 2, 5-dibromothiophene (HBrT) and 2, 5-dibromo-3, 4-difluoro-thiophene (FBrT) have been developed as solvent additives. Results show that FBrT has a high boiling point and the ability to dissolve donors and acceptors readily due to the "like dissolve like" principle, providing an effective tool in prolonging the crystallization and phase separation kinetic process of photovoltaic materials. Due to the concurrent formation of increased crystallinity, favorable phase separation, and P–i–N-like heterojunction, the FBrT-treated solar cells demonstrated improved exciton dissociation, charge transportation, extraction, and suppressed carrier recombination. Therefore, the PM6:Y6-based solar cells with FBrT additive reached an efficiency of 17.9% and fill factor of 78.6%, which are one of the highest values reached for the PM6:Y6-based binary solar cells. More strikingly, the FBrT solvent additive possesses general applicability in L8-BO, Y6-BO, and BTP-eC9-based solar cells and achieves significantly enhanced efficiencies of 18.6∼18.7% in devices. These findings make it clear that the thiophene derivatives are effective solvent additives for the further optimization of organic solar cells.